DRIP INFUSION MONITORING AND DATA LOGGING SYSTEM BASED ON YOLOv5 - Wiriasto, Giri Wahyu; Rizaldy, Andika; Wiguna, Putu Aditya; Kinasih, Indira Puteri (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
Intravenous infusion (IV) functions to deliver medication or fluids directly into the patient’s body and requires an accurate drops-per-minute (TPM) calculation to ensure the correct dosage is administered. Manual calculation techniques, which are still widely used today, tend to be inefficient and carry a high risk of human error. Therefore, a more reliable and innovative automated approach is needed. In this study, we developed a prototype of an automatic infusion monitoring system based on the CNN-YOLOv5 architecture. The system records a one-minute IV drip video using a mobile device, then processes it through a server to automatically calculate the TPM, where YOLOv5 is used for drip detection, Deep SORT for object tracking, and a unique ID numbering scheme is applied to each droplet to ensure it is counted only once until it exits the frame. The calculation results are stored in a patient database that we designed. We also explored the effect of dataset background on accuracy. Testing was conducted on 48 videos (30 fps) with two background types—white (LBP) and black (LBH)—and drip variations of 20, 30, 40, and 50 TPM with varying durations. The results showed higher accuracy on the black background, reaching 0.79 compared to 0.58 on the white background, both with a precision of 1.00. The system demonstrated excellent performance in detecting drips with high precision and good accuracy, particularly on LBP for TPM <40 fps and on LBH for TPM <50 fps.